Transcutaneous Puncture of an Undeflatable Coronary Angioplasty Balloon Catheter - Gregor Leibundgut; Christian Degen; Florian Riede (Case Reports in Cardiology)
This case report describes a quick and safe method to successfully retrieve an undeflatable angioplasty balloon via the transradial access site. The article also presents potential mechanisms of contrast media entrapment and bench tests of guidewire-assisted balloon puncture. After successful stent implantation in the proximal right coronary artery in a 74-year-old female patient referred for acute coronary syndrome, the balloon catheter became undeflatable for an unknown reason. Several attempts to burst the balloon in the guide catheter and the aorta failed. After a pullback into the radial artery, the still inflated balloon became stuck again and was unable to be retrieved through the sheath. Finally, transcutaneous puncture and aspiration of contrast media with a 23 gauge syringe needle through the skin in the right forearm allowed deflation and successful removal the balloon.